The Use of Web Blogs for English Writing class for EFL Students - Luh Putu Artini; Ni Luh Putu Eka Sulistia Dewi; Ni Wayan Juniari (Linguistic, English Education and Art (LEEA) Journal, 2022)
This research is focusing on how the web blogs use in teaching English writing class for EFL students. Learning has led students and teachers to interact at a distance through the involvement of media, platforms, and learning strategies within a complete virtual learning community. This research aims to investigate the use of Web Blog for English writing class for ELF students. This study carried out library research by conducting a literature review, where the data source used previous research on the related topic to achieve the study's objective. Four research articles published in reputable journals are listed in this research. The research aimed to determine the influence of the used web blog on the achievement of writing taken from several research articles conducted by several researcher. This study discovered that writing is one of the greatest important English abilities, and the use of web blog writing class for ELF students positively impacts English learning. The findings were derived from a literature review, where the data source was previous studies on the relevant subject. As a result, using the web blog in writing class for ELF students has a positive influence on learning writing. Keywords: Web Blog, Writing, ELF Students